Luz na passarela: a dinâmica dos eventos de moda frente ao entrelaçamento do turismo com a moda - Claudino, Adson de Lima (2023)
Fashion and tourism are contemporary phenomena that symbolize the transformations of society, arising from the socio-cultural and economic relations of their surroundings. In the quest to elucidate too much synergy between these two fields of study, the events sector stands out and, in particular, the fashion events segment. Fashion events are authentic and creative events that promote trends and innovations in the fashion chain, disseminate knowledge about the area, radiate direct and indirect benefits to other markets, collaborate for the marketing of the destinations that host them and stimulate consumption behavior by through desire, like the São Paulo Fashion Week, considered the most emblematic fashion week in Brazil. From this perspective, two questions guided this research, namely: 1) Is it possible to establish a link between the fashion and tourism markets? and; 2) How do fashion events held in Brazil enhance the tourist destinations that host them? Faced with the desire to deepen the discussions on the aforementioned theme, this dissertation aimed to investigate how fashion events collaborate with tourist activity, in order to understand the synergy between tourism and fashion. With regard to methodological aspects, this is a phenomenological research that has a descriptive and exploratory typology, with a qualitative approach. Data collection took place via the Google Meet platform, through interviews with seven professionals who work at fashion events in Brazil and a representative of the Observatório de Turismo e Eventos in the city of São Paulo. Bibliographical and documentary research was also adopted in this collection process, using content analysis as a technique for data interpretation and the Iramuteq software (version 0.7 alpha 2) for systematization and structuring of results. The results demonstrate that tourism and fashion are correlated by favoring consumption needs, behaviors and desires typical of modernity, making it possible to think of dynamics that mutually benefit them and can expand their respective sectors. Thus, fashion events are seen as events that enhance this interaction and present a prominent appreciation of Brazilian culture, user experiences, search for innovation and collaboration with other markets. The research findings point out that events of this type have skills to work with new tourism segments linked to fashion and culture, and it is opportune to develop strategies to expand these ideas. Thus, this work proposes a new look at the theme of fashion events, based on the attributes of these events as a way to expand studies in the field of tourism and fashion.